The first evidence of microplastic presence in pumice stone along the coast of Thailand: A preliminary study - Pradit, Siriporn; Puttapreecha, Ratchanee; Noppradit, Prakrit; Buranapratheprat, Anukul; Sompongchaiyakul, Penjai (Frontiers in Marine Science, 2022)
In February and March 2022, a large amount of pumice stone appeared along the shoreline of Thailand. Pumice is a type of extrusive volcanic rock, and since there are no volcanoes in the Gulf of Thailand, an interesting question was where the pumice stones originated from. Another question was whether the pumice could be a vehicle for microplastics(MP) which could then journey across the ocean until reaching the coast of Thailand. A preliminary study was begun which randomly collected samples from seven beaches in five provinces along the coast of Thailand. Grayish-green pumice stones are tiny, porous, and lightweight, ranging from 0.3–5.0 cm in size. The examination found 5.7–12.6 MP items per pumice stone. Most MP particles observed were less than 1 mm in length. From Fourier Transform Infrared Spectroscopy (FTIR) analysis, the MP were characterized as polystyrene, polypropylene, poly (ethylene terephthalate) (PET), rayon, and nylon. The MP could have entered the holes in pumice stones while floating on the water surface over long periods. From the seasonal flow patterns, it was revealed that pumice from the South China Sea was more likely to have floated with surface currents into the Gulf of Thailand.